Magnetism in a graphene-like Ising (spin-1/2) nanoparticle decorated with spin-1 atom. (1st December 2020) - Kaneyoshi, T.
ABSTRACT: The phase diagram and the thermal variations of magnetizations in a graphene-like Ising nanoparticle decorated with spin-1 atom are examined by the effective-field theory with correlations. The effects of single-ion anisotropy of spin-1 atom to the magnetic properties are discussed. The following facts are clarified, when the appropriate conditions are satisfied: The transition temperature of the nanoparticle may become larger than that of bulk honeycomb lattice. The decorated nanoparticle exhibits many characteristic phenomena observed in bulk ferrimagnetic materials.